Fluororubber composite material modified by golden yellow linear nano silicon dioxide as well as preparation method and application of fluororubber composite material

By using a template method to prepare a composite of golden-yellow linear nano-silica filler and fluororubber, the mechanical, thermal, and color properties of fluororubber were solved, and high-performance seals were prepared.

CN121064579APending Publication Date: 2025-12-05INST OF NEW MATERIALS & IND TECH WENZHOU UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511060406.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-30
Publication Date
2025-12-05

AI Technical Summary

Technical Problem

Existing technologies cannot simultaneously improve the mechanical, thermal, and color properties of golden fluororubber, and the introduction of organic dyes can lead to a decrease in mechanical and thermodynamic properties.

Method used

Golden-yellow linear nano-silica fillers were prepared using a template method and then mixed with fluororubber raw rubber to form a composite material. The performance of the composite material was optimized by controlling the content and type of nano-silica.

Benefits of technology

It significantly improves the mechanical and thermal properties of fluororubber composites, while also imparting a golden-yellow color, providing a new approach to the preparation of high-performance seals.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121064579A_ABST
    Figure CN121064579A_ABST
Patent Text Reader

Abstract

The invention provides a golden yellow linear nano silicon dioxide modified fluororubber composite material as well as a preparation method and application thereof, golden yellow silicon dioxide nanowires are successfully prepared by adopting a template method and are added into fluororubber, and the influence of different contents on the mechanics, electric conduction, heat conduction and color performance of the fluororubber composite material is researched. The synthesized novel golden yellow silicon dioxide nanowire shows excellent mechanical, thermal and color characteristic improvement effects, and a new thought is provided for development of preparation of high-performance sealing elements (such as high-strength golden yellow sealing rings).
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of high polymer materials, in particular to a golden yellow linear nano-silica modified fluororubber composite material, a preparation method and application thereof. BACKGROUND

[0002] Fluororubber is a kind of high molecular synthetic elastomer in which hydrogen atoms in side chains or main chains are partially or completely replaced by fluorine atoms. Due to the strong electronegativity of fluorine atoms and the fact that the atomic radius is almost half of the carbon-carbon bond spacing, fluorine atoms can be closely arranged around carbon atoms, so that the carbon-carbon bond (C-C) can be shielded from external substances, giving the FKM main chain excellent chemical corrosion resistance, so that FKM can be widely used in new energy vehicles, oil extraction and aerospace fields. However, with the development of society, the industry has put forward more and more stringent requirements on the mechanical properties and color performance of fluororubber. For example, the automobile oil cylinder seal puts forward higher requirements on the mechanical properties and heat resistance of fluororubber, and the need for O-ring seal anti-counterfeiting and appearance individualization puts forward requirements on the color performance of fluororubber.

[0003] At present, there are few studies and applications of golden yellow fluororubber. Golden yellow fluororubber seal has good anti-counterfeiting effect and appearance individuality, but the introduction of organic dyes in fluororubber can cause local color difference, discoloration and other problems, and directly or indirectly affect the mechanical properties, thermodynamic properties and color performance of fluororubber products. Therefore, it is necessary to design a preparation method of golden yellow fluororubber with excellent mechanical properties, thermal properties and color performance. SUMMARY

[0004] The purpose of the present application is to overcome the shortcomings and deficiencies of the prior art, and to provide a golden yellow linear nano-silica modified fluororubber composite material, a preparation method and application thereof.

[0005] The technical scheme adopted by the present application is as follows: the first aspect of the present application provides a preparation method of a golden yellow linear nano-silica modified fluororubber composite material, comprising the following steps: S1, dissolving PVP in n-pentanol, continuing to add ethanol, sodium citrate solution, methyl orange, mixing uniformly, adding sodium hydroxide and continuing to stir, then adding a silicon source, and reacting the mixed solution at 60-80℃ for 16-20h, and then centrifuging, washing and drying to obtain a golden yellow linear silica filler; S2, mixing the golden yellow linear silica filler and fluororubber raw rubber uniformly, then adding a vulcanizing agent and a vulcanizing aid to form a mixed rubber, and vulcanizing the mixed rubber to obtain a linear silica modified fluororubber composite material.

[0006] Preferably, in step S1, the mass ratio of PVP to methyl orange is (4-12):1.

[0007] Preferably, in step S1, the mass-volume ratio of PVP to n-pentanol is 1: (8-12) g / mL.

[0008] Preferably, in step S2, the ratio of fluororubber raw rubber to golden yellow linear silica filler is 100: (2.5-10).

[0009] Preferably, in step S2, the ratio of fluororubber to golden yellow linear silica filler, vulcanizing agent, vulcanizing aid is 100: (2.5-10): (0.5-1.5): (1-3).

[0010] Preferably, the silicon source is TEOS.

[0011] Preferably, in step S2, the vulcanizing agent is DHBP, and the vulcanizing aid is TAIC.

[0012] The second aspect of the present application provides a fluororubber composite material prepared by the preparation method described above.

[0013] The third aspect of the present application provides the use of the fluororubber composite material described above in a sealing ring.

[0014] The beneficial effects of the present application are as follows: The present application successfully prepares golden yellow silica nanowires by using a template method, and adds them to fluororubber, which greatly improves the mechanical, conductive and thermal properties of the fluororubber composite material, and gives the fluororubber color performance.

[0015] The results show that the methyl orange-SiO2 prepared by the template method has a typical linear structure, and the diameter is about 300 nm. When the content of methyl orange-SiO2 is 10 phr, the tensile strength and hardness of the fluororubber composite material are the highest, which are increased by 160% and 26% compared with pure fluororubber. This may be due to the nano-enhancing effect of methyl orange-SiO2 filler and the strong hardness of the filler itself. However, the addition of methyl orange-SiO2 filler hinders the movement of fluororubber molecular chains to some extent, thereby reducing the elongation at break of the fluororubber; the heating and cooling rate of the fluororubber composite material reaches a maximum value at this filler content, because methyl orange-SiO2 has higher thermal conductivity than FKM matrix, and the addition of methyl orange-SiO2 can form a three-dimensional heat conduction path in fluororubber, thereby improving the thermal conductivity of fluororubber. At this time, the fluororubber is golden yellow and has high haze.

[0016] The new golden yellow silica nanowires synthesized by the present application exhibit excellent mechanical, thermal and color performance improvement effects, and provide a new idea for the preparation of high-performance sealing elements (such as high-strength golden yellow sealing rings). BRIEF DESCRIPTION OF DRAWINGS

[0017] In order to more clearly illustrate the technical solutions of the embodiments of the present application or the prior art, the drawings needed to be used in the embodiments or prior art description will be briefly introduced. Obviously, the drawings in the following description only constitute some embodiments of the present application, and for those skilled in the art, other drawings obtained according to these drawings without creative labor are still within the scope of the present application.

[0018] Figure 1 (a) infrared spectra of methyl orange, SiO2 and methyl orange modified SiO2, (b) physical picture of methyl orange-SiO2 filler; Figure 2 (a) methyl orange, (b) SiO2, (b) SEM of methyl orange-SiO2; Figure 3 is the mechanical properties of the fluororubber prepared in Example 1-4 and Comparative Example 1; Figure 4 (a) tensile strength, (b) elongation at break and (c) hardness of the fluororubber prepared in Example 4 and Comparative Example 2; Figure 5 The cross-section morphology of the FKM prepared in Comparative Example 1 and Examples 1-4; Figure 6 The infrared spectra of the FKM prepared in Comparative Example 1 and Examples 1-4; Figure 7 (a) temperature rising and falling infrared imaging, (b, c) temperature rising and falling curves of the FKM prepared in Comparative Example 1 and Examples 1-4; Figure 8 (a) light transmittance and haze, (b) physical picture of the FKM prepared in Comparative Example 1 and Examples 1-4. DETAILED DESCRIPTION

[0019] In order to make the objects, technical solutions and advantages of the present application clearer, the present application will be further described in detail below with reference to the drawings.

[0020] Example 1 The present embodiment provides a preparation method of golden yellow linear nanosilica modified fluororubber composite material, comprising the following steps: S1. Take 4g PVP (polyvinylpyrrolidone) and 40ml n-pentanol into a container and mix, put the container with the mixed solution into an ultrasonic device, and ultrasonic for 2h until the PVP is completely dissolved; after the ultrasonic ends, sequentially add 3ml ethanol, 0.5ml sodium citrate solution (0.18mol / L), and 0.5g methyl orange into the container, stir for 10 minutes; add 1ml NaOH into the container, continue to stir for 20 minutes; add 4ml tetraethoxysilane into the container, and place the container on a magnetic stirrer, set the temperature to 70°C, and stir for 18 hours; after the reaction ends, separate the solid by centrifugation, and wash with anhydrous ethanol and water three times each, and finally dry the obtained golden yellow solid at 60°C to obtain a golden yellow linear nanosilica filler, i.e. methyl orange-SiO2 filler.

[0021] S2. Start the open mill, set the roll temperature to 50°C, let the roll preheat to the specified temperature and keep stable, adjust the roll gap to 0.5mm, and add 100 parts by mass of fluororubber raw rubber, so that it is subjected to strong shearing and extrusion between the rolls for plasticizing; put 2.5 parts by mass of the golden yellow linear nanosilica filler into the open mill, and continuously turn the raw materials to make them plasticize uniformly; then add 1 part by mass of the curing agent DHBP and 2 parts by mass of the co-curing agent TAIC into the open mill in sequence, and mix the compounding agent and the raw materials by turning and triangle bagging during the addition; adjust the roll gap to 0.8mm, take the mixed rubber out of the open mill, and cut the rubber sheet into 25g square rubber sheets with a knife; put the rubber sheets into a flat vulcanizing machine at 170°C for one-stage vulcanization for 10 minutes, and then put them into an oven at 200°C for two-stage vulcanization for 24 hours to obtain a golden yellow fluororubber, which is recorded as FKM / 2.5phr-methyl orange SiO2.

[0022] Example 2 The difference between this example and Example 1 is only that in step S2, 5 parts by mass of the golden yellow linear nanosilica filler is added, and the obtained fluororubber is recorded as FKM / 5phr-methyl orange SiO2.

[0023] Example 3 The difference between this example and Example 1 is only that in step S2, 7.5 parts by mass of the golden yellow linear nanosilica filler is added, and the obtained fluororubber is recorded as FKM / 7.5phr-methyl orange SiO2.

[0024] Example 4 The difference between this example and Example 1 is only that in step S2, 10 parts by mass of the golden yellow linear nanosilica filler is added, and the obtained fluororubber is recorded as FKM / 10phr-methyl orange SiO2.

[0025] Comparative Example 1 The difference between the present comparative example and Example 1 is that step S1 is not performed, and in step S2, no golden yellow linear nanosilica filler is added, and the fluororubber prepared is pure FKM.

[0026] Comparative Example 2 The difference between the present comparative example and Example 4 is that in step S1, no methyl orange is added, and the fluororubber prepared is denoted as FKM / 10phr-SiO2.

[0027] Filler morphology characterization As shown in Figure Figure 1 (a), the infrared spectrum test results of methyl orange, SiO2 and methyl orange modified SiO2 are shown, respectively. Pure SiO2 presents typical Si-O-Si absorption peaks in the range of 800 cm -1 -1300 cm -1 , and there is basically no obvious absorption in other wave bands. In the infrared spectrum of methyl orange modified SiO2, in addition to the basic structural characteristics of SiO2, some new absorption peaks also appear, especially in the range of about 1350-1750 cm -1 . These new absorption peaks may be derived from the new chemical environment formed between the -C=O group or aromatic ring in the methyl orange molecule and the SiO2 surface hydroxyl, or may be related to the new vibration mode caused by the vibration of the aromatic ring C=C skeleton and the interaction between the amine group (-NH2) and SiO2. These characteristic peaks do not exist in pure SiO2, but only appear in the modified product, further proving that the methyl orange molecules have successfully combined or adsorbed on the surface of SiO2.

[0028] In summary, through comparative analysis of the infrared spectra before and after modification, the appearance of new absorption peaks, and the slight shift and intensity change of Si-O-Si characteristic peaks, all can be used as strong evidence for the successful modification of methyl orange on the surface of SiO2, indicating that the modification reaction proceeds smoothly and forms a stable methyl orange-SiO2 composite filler.

[0029] Figure 2 The SEM images of methyl orange, SiO2 and methyl orange-SiO2 are shown. Figure 2 In Figure (a), the methyl orange presents a granular irregular accumulation morphology. Figure 2 Figure (b) is linear silica (diameter about 300 nm), and its structure presents a typical linear interlaced and entangled morphology, and the linear particles of different lengths constitute a loose and porous network structure. Figure 2(c) The linear silica modified by methyl orange, as can be seen from the image, has basically the same overall morphology as before modification, still maintaining a good linear structure and network distribution, and no obvious change in morphology is observed. This shows that the introduction of methyl orange does not significantly destroy or reconfigure the original linear structure of silica.

[0030] Mechanical properties of fluoroelastomer composites In order to explore the influence of methyl orange-SiO2 filler content on the mechanical properties of fluororubber composites, the tensile strength, elongation at break and hardness of different samples were tested by electronic universal testing machine and hardness tester, respectively. Figure 3 (a) and Figure 3 (b) shows that with the increase of methyl orange-SiO2 filler content, the tensile strength and hardness of fluororubber gradually increase, while the elongation at break gradually decreases. When the content of methyl orange-SiO2 filler reaches 10 phr, the tensile strength and hardness of fluororubber reach the maximum value, which is increased by 160% and 26% compared with pure fluororubber, respectively. This may be due to the nano-enhancing effect of methyl orange-SiO2 filler and the strong hardness of the filler itself. However, the addition of methyl orange-SiO2 filler hinders the movement of fluororubber molecular chain to some extent, thereby reducing the elongation at break.

[0031] In order to explore the influence of the presence of methyl orange in methyl orange-SiO2 filler on the mechanical properties of fluororubber, the tensile strength, elongation at break and hardness of FKM / 10 phr-methyl orange SiO2 prepared in Example 4 and FKM / 10 phr-SiO2 prepared in Comparative Example 2 were tested, and the results are shown in Figure 4 (a). Figure 4 (a) shows that the addition of methyl orange has no significant effect on the tensile strength of fluororubber composite. Figure 4 (b) shows that the elongation at break of FKM / 10 phr-methyl orange SiO2 and FKM / 10 phr-SiO2 is 260.98% and 261.66% respectively, with a difference of only 0.68%, which can be ignored within the experimental error range, indicating that the introduction of methyl orange has no obvious effect on the elongation at break. Figure 4 (c) shows that the Shore hardness of FKM / 10 phr-methyl orange SiO2 and FKM / 10 phr-SiO2 is 68, indicating that the addition of methyl orange has no significant effect on the hardness. In summary, the presence of methyl orange in methyl orange-SiO2 filler has negligible effect on the mechanical properties of fluororubber.

[0032] Fracture morphology analysis of fluoroelastomer composites The micro-morphology of the macro-tensile fracture surface of the composite under different filler contents is shown in Figure 5As shown, by analyzing the fracture surface morphology, the influence mechanism of methyl orange-SiO2 content on the fracture behavior of FKM composites can be determined.

[0033] From Figure 5 As shown in (a), the fracture surface of pure FKM is relatively flat, showing typical brittle fracture characteristics, with a small amount of stress whitening area, but no obvious dimple or fiber structure. The absence of filler particles and the good uniformity of the matrix may be due to the lack of reinforcing phase in pure FKM, which has weak crack propagation resistance and low fracture energy. As shown in (b), the fracture surface roughness of FKM / 2.5 phr-methyl orange SiO2 increases, and shallow dimples appear, indicating an increase in toughness. A small amount of SiO2 particles are uniformly dispersed without obvious agglomeration. The matrix and filler have good interfacial bonding without debonding. It is concluded that low content of modified SiO2 effectively improves the toughness of the material, and the filler is well dispersed, showing significant reinforcement. Figure 5 As shown in (c), FKM / 5 phr-methyl orange SiO2 has deeper and denser dimples, showing typical ductile fracture characteristics. SiO2 particles are uniformly distributed (consistent in size without aggregation) and tightly bonded to the matrix, with a small amount of micropores but no continuous cracks. The filler content is moderate, the interfacial bonding and dispersion are optimal, and the comprehensive mechanical properties are optimal. Figure 5 As shown in (d), FKM / 7.5 phr-methyl orange SiO2 has reduced number of dimples and local small-size agglomerates. The matrix shows a slight shear band, indicating a decrease in plastic deformation capacity. The crack initiation point may be from the agglomeration area. It may be due to the filler content close to the critical value, and the dispersion starts to deteriorate, but still maintains some reinforcement effect. Figure 5 As shown in (e), FKM / 10 phr-methyl orange SiO2 has a flat fracture surface, returning to a brittle fracture mode with randomly distributed large-size holes. SiO2 significantly agglomerates, and the interface debonding is obvious. The crack propagates along the filler-matrix interface, forming a river-like pattern, which may be due to excessive filler leading to severe agglomeration, becoming a stress concentration source, and the material performance deteriorates. Figure 5

[0034] Electrical conductivity properties of fluoroelastomer composites To investigate the effect of methyl orange-SiO2 content on the electrical conductivity of fluorine rubber, the volume resistivity of different fluorine rubber composites was tested by digital multimeter, and the results are shown in Table 1. As shown in Table 1, the addition of methyl orange-SiO2 can improve the volume resistivity of fluorine rubber composites to some extent, reducing the electrical conductivity of fluorine rubber, which is mainly due to the insulating property of methyl orange-SiO2 itself. Table 1 Electrical properties of different samples

[0035] Electrical conductivity properties of fluoroelastomer composites ​To investigate the effect of methyl orange-SiO2 content on the conductive properties of fluororubber, the volume resistivity of different fluororubber composites was tested by using a digital multimeter, and the results are shown in Table 2. As shown in Table 2, the addition of methyl orange-SiO2 can improve the volume resistivity of fluororubber composites to some extent, and reduce the conductive properties of fluororubber, which is mainly due to the insulation of methyl orange-SiO2 itself.

[0036] Table 4 Conductive properties of different samples Infrared analysis of fluoroelastomer composites Figure 6 The infrared spectra of FKM with different contents of methyl orange-SiO2 are shown in the figure. As shown in the figure, for pure FKM, a strong absorption peak appears in the range of 1140-1240 cm -1 , which is attributed to the stretching vibration of C-F bond, which is the characteristic peak of FKM, reflecting the chemical structure of its fluorocarbon backbone. The weak peaks at 2920 cm -1 and 2850 cm -1 are attributed to the vibration of a small amount of non-fluorinated C-H bonds in FKM (such as crosslinking agent residues). In addition, C-C skeleton vibration and C-F bending vibration may exist at 1400-1500 cm -1 and 500-800 cm -1 , respectively. For FKM / 2.5 phr-methyl orange SiO2, a weak broad peak appears near 1100 cm -1 , which is attributed to the vibration of Si-O-Si. Weak peaks appear at 1610 cm -1 and 1490 cm -1 , corresponding to N=N and benzene ring vibration, indicating that a small amount of methyl orange molecules successfully modified SiO2 and dispersed in FKM. Compared with pure FKM, the C-F peak (1140-1240 cm -1 ) does not shift, but the peak width increases slightly, which may be related to the local restriction of molecular chains caused by the introduction of fillers. The Si-O-Si peak shifts to about 5 cm -1 lower wave number (to 1095 cm -1 ), indicating that there is a hydrogen bond interaction between methyl orange-SiO2 and FKM. With the increase of filler concentration, the Si-O-Si peak intensity increases, and the peak intensity at 1100 cm -1 significantly increases, indicating that the dispersibility of SiO2 in the matrix is improved. The N=N peak is clear, and the peak intensity at 1610 cm -1 increases, confirming that the amount of methyl orange modification increases, and the surface loading is more sufficient.

[0037] Thermal properties of fluoroelastomer composites The effect of methyl orange-SiO2 filler content on the thermal stability of the material can be revealed by analyzing the heating and cooling curves of the fluororubber and its methyl orange-SiO2 filled fluororubber composite during heating and cooling. As can be seen from the above figure, compared with the pure FKM material, the addition of methyl orange-SiO2 filler can significantly improve the heating and cooling rate of FKM, especially when the content of methyl orange-SiO2 filler reaches 10 phr, the heating and cooling rate of the fluororubber composite reaches the maximum. This is because methyl orange-SiO2 has higher thermal conductivity than FKM matrix, and the addition of methyl orange-SiO2 can form a three-dimensional heat conduction path in the fluororubber, thereby improving the thermal conductivity of the fluororubber.

[0038] Color properties analysis of fluoroelastomer composites Haze and light transmittance can reflect the turbidity and sharpness of the composite material, so these two parameters are often used to characterize the optical performance of fluororubber composite. By adding different contents of methyl orange-SiO2 nano filler to fluororubber, the effect of methyl orange-SiO2 nano filler on the light transmittance and haze of the material was investigated, and the results are shown in Figure 8 . As can be seen from Figure 8 (a), the light transmittance decreases with the increase of the content of methyl orange-SiO2 nano filler, which may be due to the easy agglomeration of methyl orange-SiO2 nano filler, forming a heterogeneous interface and enhancing light scattering; the haze increases with the increase of the content of methyl orange-SiO2 nano filler, indicating that the internal scattering of the material is enhanced. Therefore, the introduction of methyl orange-SiO2 nano filler significantly affects the optical performance of fluororubber. As can be seen from Figure 8 (b), the original fluororubber is white, with the highest light transmittance and the lowest haze. After adding methyl orange-SiO2 nano filler, the color of the fluororubber is golden yellow.

[0039] Color brightness (L * ), hue angle (h), red-green color (a * ), and yellow-blue color (b * ) are the basic color parameters of fluororubber composite materials, which play an important role in the application of fluororubber. As can be seen from Figure 8 (c), by analyzing the color brightness (L * ), the left value decreases from 100 to 0, which may correspond to the significant decrease of the brightness of fluororubber with the increase of the concentration of methyl orange-SiO2 filler. For example, the sample without methyl orange-SiO2 filler has the highest color brightness, while the sample with high concentration of filler tends to 0. The methyl orange-SiO2 filler may be golden yellow particles, but high content may lead to agglomeration or increase of surface roughness, reducing the light reflectivity of the material and making its color darker.

[0040] As can be seen from Figure 8(d) It can be seen that the red-green chroma of the fluoroelastomer composites with low content of methyl orange-SiO2filler is high (a*≈80-100), and the hue is close to yellow (b*is high), indicating that the filler is uniformly dispersed and has little interference with the color. The brightness of the fluoroelastomer composites with high content of methyl orange-SiO2filler decreases significantly (a*≈0-20), and the hue may be red (b*is low), indicating that the filler agglomerates or reacts with the matrix, resulting in deepening of the color and accompanying hue shift. In summary, the content of methyl orange-SiO2filler significantly affects the color performance of the fluoroelastomer: low content makes the material bright and the hue stable, and high content reduces the brightness and the hue may shift to red.

[0041] The above disclosure is only the preferred embodiment of the present application, of course, cannot be limited by this to limit the scope of the present application, therefore, the equivalent changes made according to the claims of the present application, still belongs to the scope covered by the present application.

Claims

1. A method for preparing a gold yellow linear nanosilica modified fluororubber composite material, characterized in that, Comprising the following steps: S1, dissolving PVP in n-pentanol, continue to add ethanol, sodium citrate solution, methyl orange, mix evenly, add sodium hydroxide and continue to stir, then add silicon source, the mixed solution is reacted at 60-80℃ for 16-20h, centrifugal washing and drying to obtain golden yellow linear silica filler; S2, mixing the golden yellow linear silica filler with fluororubber raw rubber evenly, then adding vulcanizing agent and vulcanizing aid to form mixed rubber, vulcanizing the mixed rubber to obtain linear silica modified fluororubber composite material.

2. The method for preparing a gold yellow linear nanosilica modified fluororubber composite according to claim 1, characterized in that: In step S1, the mass ratio of PVP to methyl orange is (4-12):

1.

3. The method for preparing a gold yellow linear nanosilica modified fluororubber composite according to claim 1, characterized in that: In step S1, the mass-volume ratio of PVP to n-pentanol is 1:(8-12)g / mL.

4. The method of claim 1, wherein the method is characterized by: In step S2, the ratio of fluororubber raw rubber to golden yellow linear silica filler is 100:(2.5-10).

5. The method of claim 1, wherein the method is characterized by: In step S2, the ratio of fluororubber to golden yellow linear silica filler, vulcanizing agent and vulcanizing aid is 100:(2.5-10):(0.5-1.5):(1-3).

6. The method of claim 1, wherein the method is characterized by: The silicon source is TEOS.

7. The method of claim 1, wherein the method is characterized by: In step S2, the vulcanizing agent is DHBP and the vulcanizing aid is TAIC.

8. A fluoroelastomer composite, characterized by: It is prepared by the preparation method of any one of claims 1-7.

9. The fluororubber composite material of claim 8 is used in sealing ring.